Fracture and fatigue of materials and structures : selected, peer reviewed papers from the 14th Polish Conference on Fracture Mechanics and Fatigue, September 23-26, 2013, Kielce-Cedzyna, Poland - Galkiewicz, Jaroslaw (Key engineering materials ;, 2014)
The volume on Fracture Mechanics mostly presents papers concerning research problems in the field of fatigue. Fracture mechanics is the subject of about 28% of all papers. In several articles new, sometimes futuristic, experimental techniques were shown. Temporary description, more details to follow.